CLINICAL EFFECTIVENESS OF MICROCURRENT REFLEXOTHERAPY IN THE CORRECTION OF BEHAVIORAL DISORDERS IN CHILDREN WITH AUTISM (Herald of the National Children's Medical Center, 2022)
Children's autism is one of the urgent health problems in the world, which is determined not so much by the frequency of childhood autism (DA) in the child population - from 4 to 26 per 10,000 children, but by social significance.The purpose: to study the effectiveness of microcurrent reflexotherapy in children with ASD.Materials and methods. The study is based on the survey data of 100 children with autism. The diagnosis of ASD in the study groups was determined using DSM-IV criteria for the diagnosis of autistic disorder. The age of the children ranged from 2 to 18 years. The main group consisted of 50 children with autism who received MTRTsessions. The comparison group consisted of 50 children with autism who received standard pharmacotherapy.Conclusion: in the treatment of ASD in children, the appointment of MTRT in complex treatment with pharmacotherapy and ABA therapy allows to improve the work of those parts of the brain that are responsible for speech and the desire to make contact. The improvement is characterized by the following: vocabulary expands, phrases and sentences appear, diction improves, learning ability increases. Children with more pronounced developmental delays and autism at first gradually have a desire to make contact, they begin to understand speech and fulfill simple requests, social skills develop.
Keywords: autism spectrum disorders; autism; children; neurological status; treatment; microcurrent reflexotherapy